In Vivo Imaging of Far-red Fluorescent Proteins after DNA Electrotransfer to Muscle Tissue - Hojman Pernille; Eriksen Jens; Gehl Julie (Biological Procedures Online, 2009)
Abstract DNA electrotransfer to muscle tissue yields long-term, high levels of gene expression; showing great promise for future gene therapy. We want to characterize the novel far-red fluorescent protein Katushka as a marker for gene expression using time domain fluorescence in vivo imaging. Highly efficient transgenic expression was observed after DNA electrotransfer with 100-fold increase in fluorescent intensity. The fluorescent signal peaked 1 week after transfection and returned to background level within 4 weeks. Katushka expression was not as stable as GFP expression, which was detectable for 8 weeks. Depth and 3D analysis proved that the expression was located in the target muscle. In vivo bio-imaging using the novel Katushka fluorescent protein enables excellent evaluation of the transfection efficacy, and spatial distribution, but lacks long-term stability.